Cultural Adaptation Strategies in Illiteracy Eradication Programs: Insights from North Toraja, Indonesia - Daud Chrismanto Baratau (IHSA Institute, 2024)
This research explores the role of cultural adaptation in the illiteracy eradication program in North Toraja, Indonesia. Through a comprehensive investigation, the study aims to understand how cultural factors influence the implementation and effectiveness of literacy initiatives in this unique cultural context. By examining the attitudes, perceptions, and experiences of various stakeholders, including community members, educators, and policymakers, the research seeks to provide insights that can inform the development of more effective and culturally sensitive literacy programs in the region. The research employs a mixed-methods approach, combining qualitative and quantitative data collection methods. Preliminary findings suggest that the program has been successful in promoting literacy skills among participants, with improvements reported in reading and writing abilities. Community engagement has been a significant factor in the program's success, with community members expressing a strong sense of ownership and investment in the program. Cultural adaptation has also played a crucial role, with program materials and delivery reflecting local cultural values, traditions, and languages. The implications of the findings for future literacy programs in North Toraja and similar cultural contexts are discussed. Recommendations for policymakers, educators, and practitioners are provided to enhance cultural adaptation, promote community engagement, and address systemic inequalities in education.